PENGARUH PDRB DAN JUMLAH PENDUDUK TERHADAP PENDAPATAN ASLI DAERAH KABUPAREN MERANGIN - Evi Adriani; Sri Indah Handayani (Universitas Batanghari Jambi, 2008)
The research used secondary information that analyzed by regression method to have a simple picture about relationship between population growth, gross domestic regional product, and local revenue of Region of Merangin.The conclusion of this research shows us a positive relationship between gross domestic regional product and population growth in influencing local revenue of a region. The variable of gross domestic regional product (x1), represented by elastic coefficient, has 2,197 point where t variable has 8,868 point means this variable has significant influence to local revenue variable. In the other side, population growth (x2) has minus 0,794 point as its elastic coefficient where t variable has minus 1,020 point, and it means this variable does not have significant influence to variable of local revenue. The F variable, a examiner value, has 61.132 point, it tells us that gross domestic regional product and population growth fairly together gives an influence to local revenue of Region of Merangin.Entirely, by using regression analyzes we have found that local revenue would be influenced by fluctuation of economic growth and population growth as reflected by values of gross domestic regional product. Key word : local revenue, gross domestic regional product, population growth, regression